1975
DOI: 10.1002/pol.1975.170130920
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of poly(tetramethyl‐p‐silphenylene) siloxane homopolymers and copolymers in nitrogen

Abstract: The thermogravimetry (TGA) in nitrogen was measured for poly(tetramethyl‐p‐silphenylene)‐siloxane (TMPS) fractions with narrow molecular weight distributions and for block copolymers of TMPS and dimethyl siloxane (DMS) with varying composition. The measurements were made with the Perkin‐Elmer DCS IB‐TGA attachment which consists of a Cahn electrobalance and a wire‐wound furnace with programmable temperature controls. The weight loss curves for heating rates of 10, 20, and 40°C/min were analyzed using the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It was revealed that the melt polycondensation and simultaneous cross-linking reaction were effective to obtain the polysilarylenesiloxanes which have high thermal degradation temperature and high thermomechanical stability. [doi:10.1295/polymj.PJ2006004] KEY WORDS Polysilarylenesiloxane / Melt Polycondensation / Thermal Stability / Glass Transition / Thermomechanical Stability / Polysilarylenesiloxanes 1,2 and their copolymers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have been investigated as high temperature elastomers. The common characteristics of these polymers are their high thermal degradation temperatures (T d 's) and low glass transition temperatures (T g 's), which are attributed to their flexible tetramethyldisiloxane units in the main chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that the melt polycondensation and simultaneous cross-linking reaction were effective to obtain the polysilarylenesiloxanes which have high thermal degradation temperature and high thermomechanical stability. [doi:10.1295/polymj.PJ2006004] KEY WORDS Polysilarylenesiloxane / Melt Polycondensation / Thermal Stability / Glass Transition / Thermomechanical Stability / Polysilarylenesiloxanes 1,2 and their copolymers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have been investigated as high temperature elastomers. The common characteristics of these polymers are their high thermal degradation temperatures (T d 's) and low glass transition temperatures (T g 's), which are attributed to their flexible tetramethyldisiloxane units in the main chain.…”
mentioning
confidence: 99%
“…The common characteristics of these polymers are their high thermal degradation temperatures (T d 's) and low glass transition temperatures (T g 's), which are attributed to their flexible tetramethyldisiloxane units in the main chain. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These characteristics are desirable for an elastomer, and are, however, undesirable for the heat-resistant materials such as a high-temperature coating and a low dielectric insulation material in semiconductor devices because the thermomechanical stability of these polymers is not enough at high temperature. Therefore, polysilarylenesiloxanes and their copolymers have never been used nothing but elastomers.…”
mentioning
confidence: 99%
“…c) A soluble part was obtained by the Soxhlet extraction method from the insoluble product. Polymer P2 [3] . It was suggested from this result that the cross-linking reaction would occur even in 0.1 M dilute solution and the part having relatively low degree of cross-linking was dissolved in THF.…”
Section: Hydrosilylation Polymerizationmentioning
confidence: 99%
“…. a) [3] 0 means the initial concentration of the monomer 3. b) M n (number-average molecular weight) and M w (weight-average molecular weight) were determined by GPC. c) A soluble part was obtained by the Soxhlet extraction method from the insoluble product.…”
Section: Hydrosilylation Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation